Toward Smart Microalgae Cultivation: The Role of Machine Learning and Data Science - Zhi Lin Lau; Kian Wah Liew; Tomas Maul; Doris Ying Ying Tang; Pau Loke Show; Kit Wayne Chew; Yee Jiun Yap (Journal of Environmental Chemical Engineering, 2026)

Retraction notice to ‘Biodegradation of crude oil in seawater by using a consortium of symbiotic bacteria’ [Environ. Res. 213 (2022) 113721] - Lai Fatt Chuah; Kit Wayne Chew; Awais Bokhari; Muhammad Mubashir; Pau Loke Show (Environmental Research, 2026)

Retraction notice to ‘Source, occurrence, distribution, fate, and implications of microplastic pollutants in freshwater on environment: A critical review and way forward’ [Chemosphere 325 (2023) 138367] - Tonni Agustiono Kurniawan; Ahtisham Haider; Hafiz Muhammad Ahmad; Ayesha Mohyuddin; Hafiz Muhammad Umer Aslam; Sohail Nadeem; Mohsin Javed; Mohd Hafiz Dzarfan Othman; Hui Hwang Goh; Kit Wayne Chew (Chemosphere, 2026)

Retraction notice to “Advancement of green technologies: A comprehensive review on the potential application of microalgae biomass” [Chemosphere 281, October 2021, 130886] - Jiunn Kwok Yap; Revathy Sankaran; Kit Wayne Chew; Heli Siti Halimatul Munawaroh; Shih-Hsin Ho; J. Rajesh Banu; Pau Loke Show (Chemosphere, 2025)

Retraction notice to “Comparative study of ozonation and ozonation catalyzed by Fe-loaded biochar as catalyst to remove methylene blue from aqueous solution” [Chemosphere 307 Part 1, November 2022, 135738] - Muhammad Babar; Hafiz Muhammad Shahzad Munir; Aamna Nawaz; Naveed Ramzan; Umair Azhar; Muhammad Sagir; Muhammad Suleman Tahir; Amir Ikhlaq; Siti Nuurul huda Mohammad Azmin; Muhammad Mubashir; Kuan Shiong Khoo; Kit Wayne Chew (Chemosphere, 2025)

Ocean acidification changes the interspecific competition of Sargassum fusiforme and Ulva lactuca by regulating carbon and nitrogen metabolism - Cong Cao; Dongya Bao; Lili Xu; Zengling Ma; Mingjiang Wu; Guang Gao; Kit Wayne Chew; Shuaipeng Tian; Binbin Chen (Harmful Algae, 2025)

Retraction notice to “Pyrolysis: An effective technique for degradation of COVID-19 medical wastes” [Chemosphere 275 (2021) 130092] - Selvakumar Dharmaraj; Veeramuthu Ashokkumar; Rajesh Pandiyan; Heli Siti Halimatul Munawaroh; Kit Wayne Chew; Wei-Hsin Chen; Chawalit Ngamcharussrivichai (Chemosphere, 2025)

Retraction notice to “Utilization of agricultural lignocellulosic wastes for biofuels and green diesel production” [Chemosphere 290(2022) 133246] - Chaitanya Kumar Reddy Pocha; Shir Reen Chia; Wen Yi Chia; Apurav Krishna Koyande; Saifuddin Nomanbhay; Kit Wayne Chew (Chemosphere, 2025)

Impact of Carbon and Nitrogen Assimilation in Sargassum fusiforme (Harvey) Setchell due to Marine Heatwave Under Global Warming - Xingda Sheng; Xiaojie Zuo; Lin Luo; Guanfeng Pang; Huawei Zhang; Kit Wayne Chew; Dongshun Fang; Binbin Chen; Mingjiang Wu (Global Change Biology, 2025)
Because of the rising global temperatures, Sargassum fusiforme (Harvey) Setchell, a commercially valuable seaweed, has experienced reduced yield and quality due to high temperatures from marine heatwave events. However, the mechanisms underlying the effects of heatwave stress on S. fusiforme remain unclear. In this study, the mechanisms of heatwave stress on the carbon and nitrogen assimilation processes in S. fusiforme were analyzed. These results indicated that heatwave stress, especially at 30°C for 12 days, significantly increased the levels of hydrogen peroxide (83%), malondialdehyde (84.7%), and relative conductivity (16.5%) in algae, which suggested an increase in algal damage. Morphologically, heatwave stress damaged the thylakoid structure and reduced the photosynthetic efficiency of algae and accumulated NADPH, ATP, and α‐ketoglutarate significantly, resulting in decreased content of mannitol, the photosynthetic product. Additionally, physiological and transcriptomic results revealed that heatwave stress inhibited the rate of nitrate absorption rate and the activities of the most enzymes associated with nitrogen accumulation, while significantly upregulating glutamate dehydrogenase (GDH), suggesting a crucial role for GDH in S. fusiforme 's adaptation to heatwave stress. In terms of amino acid composition, proline and alanine were the most sensitive to heatwave treatment. Moreover, under the natural heatwave environment simulation validation experiment, the algae showed the same physiological performance as under laboratory conditions. The results indicated that marine heatwave events increased oxidative damage in S. fusiforme and inhibited carbon and nitrogen absorption and assimilation, ultimately leading to negative effects on the growth of algae. Thus, in the context of rapid global warming exacerbating marine heatwave events, our study provides valuable insights for high‐temperature‐resistant breeding and ecological management in coastal aquaculture.

Role of macroalgal blue carbon ecosystems in climate change mitigation - Samadder Chandrani; Dey Drishanu; Ganesh Vaishnavi; Sathaiah Gunaseelan; Balasubramaniem Ashokkumar; Kannan Selvi Uma Bharathi; Kit Wayne Chew; Perumal Varalakshmi (Science of The Total Environment, 2025)

Comprehensive techno-economic and environmental assessment for 2,3-butanediol production from bread waste - Bikash R Tiwari; Sunil K. Maity; Satinder K Brar; Kit Wayne Chew; Gopalakrishnan Kumar; Vinod Kumar (Chemical Engineering Journal, 2024)

Nanomaterials in aquaculture disinfection, water quality monitoring and wastewater remediation - Silvanir; Wei Han Foo; Wen Yi Chia; Stephan Ende; Shir Reen Chia; Kit Wayne Chew (Journal of Environmental Chemical Engineering, 2024)

Digitalised prediction of blue pigment content from Spirulina platensis: Next-generation microalgae bio-molecule detection - Jun Wei Roy Chong; Kuan Shiong Khoo; Kit Wayne Chew; Huong-Yong Ting; Koji Iwamoto; Pau Loke Show (Algal Research, 2024)

Deep eutectic solvents as sustainable extraction media for extraction of polysaccharides from natural sources: Status, challenges and prospects - Noorfatimah Yahaya; Ahmad Husaini Mohamed; Muhammad Sajid; Nur Nadhirah Mohamad Zain; Pao-Chi Liao; Kit Wayne Chew (Carbohydrate Polymers, 2024)

In silico antiviral properties of Spirulina platensis phycobiliprotein and phycobilin as natural inhibitor for SARS-CoV-2 - Heli Siti Halimatul Munawaroh; Gun Gun Gumilar; Riska Nur Pratiwi; Selmi Fiqhi Khoiriah; Andriati Ningrum; Larasati Martha; Kit Wayne Chew; Pau-Loke Show (Algal Research, 2024)

Artificial intelligence-driven microalgae autotrophic batch cultivation: A comparative study of machine and deep learning-based image classification models - Jun Wei Roy Chong; Kuan Shiong Khoo; Kit Wayne Chew; Huong-Yong Ting; Koji Iwamoto; Roger Ruan; Zengling Ma; Pau Loke Show (Algal Research, 2024)

Leveraging food waste for electricity: A low-carbon approach in energy sector for mitigating climate change and achieving net zero emission in Hong Kong (China) - Tonni Agustiono Kurniawan; Xue Liang; Hui Hwang Goh; Mohd Hafiz Dzarfan Othman; Abdelkader Anouzla; Hussein E. Al-Hazmi; Kit Wayne Chew; Faissal Aziz; Imran Ali (Journal of Environmental Management, 2024)

Hydrogen production and pollution mitigation: Enhanced gasification of plastic waste and biomass with machine learning & storage for a sustainable future - Abu Danish Aiman Bin Abu Sofian; Hooi Ren Lim; Kit Wayne Chew; Kuan Shiong Khoo; Inn Shi Tan; Zengling Ma; Pau Loke Show (Environmental Pollution, 2024)

Application of high shear-assisted liquid biphasic system for protein extraction from Chlorella sp - Silvanir; Sin Yuan Lai; Azren Aida Asmawi; Kit Wayne Chew; Cheng Loong Ngan (Bioresource Technology, 2024)

Nickel-rich nickel–cobalt–manganese and nickel–cobalt–aluminum cathodes in lithium-ion batteries: Pathways for performance optimization - Abu Danish Aiman Bin Abu Sofian; Ibnu Syafiq Imaduddin; S.R. Majid; Tonni Agustiono Kurniawan; Kit Wayne Chew; Chyi-How Lay; Pau Loke Show (Journal of Cleaner Production, 2024)

Net zero emission in circular bioeconomy from microalgae biochar production: A renewed possibility - Guowei Wu; Pei En Tham; Kit Wayne Chew; Heli Siti Halimatul Munawaroh; Inn Shi Tan; Wan Abd Al Qadr Imad Wan-Mohtar; Malinee Sriariyanun; Pau Loke Show (Bioresource Technology, 2023)

Decarbonization in waste recycling industry using digitalization to promote net-zero emissions and its implications on sustainability - Tonni Agustiono Kurniawan; Mohd Hafiz Dzarfan Othman; Xue Liang; Hui Hwang Goh; Petros Gikas; Tutuk Djoko Kusworo; Abdelkader Anouzla; Kit Wayne Chew (Journal of Environmental Management, 2023)

Insights of microalgae-based aquaculture feed: A review on circular bioeconomy and perspectives - Pei En Tham; Hooi Ren Lim; Kuan Shiong Khoo; Kit Wayne Chew; Yee Jiun Yap; Heli Siti Halimatul Munawaroh; Zengling Ma; Saravanan Rajendran; Lalitha Gnanasekaran; Pau Loke Show (Algal Research, 2023)

RETRACTED: Source, occurrence, distribution, fate, and implications of microplastic pollutants in freshwater on environment: A critical review and way forward - Tonni Agustiono Kurniawan; Ahtisham Haider; Hafiz Muhammad Ahmad; Ayesha Mohyuddin; Hafiz Muhammad Umer Aslam; Sohail Nadeem; Mohsin Javed; Mohd Hafiz Dzarfan Othman; Hui Hwang Goh; Kit Wayne Chew (Chemosphere, 2023)

Thermochemical conversion of different biomass feedstocks into hydrogen for power plant electricity generation - Chaitanya Kumar Reddy Pocha; Wen Yi Chia; Silvanir; Tonni Agustiono Kurniawan; Kuan Shiong Khoo; Kit Wayne Chew (Fuel, 2023)

Editorial: Special issue on “Algal biotechnology” - Kit Wayne Chew; Pau Loke Show (Biocatalysis and Agricultural Biotechnology, 2023)

Challenges and opportunities for biochar to promote circular economy and carbon neutrality - Tonni Agustiono Kurniawan; Mohd Hafiz Dzarfan Othman; Xue Liang; Hui Hwang Goh; Petros Gikas; Kok-Keong Chong; Kit Wayne Chew (Journal of Environmental Management, 2023)

Nanotechnology for improved production of algal biofuels: a review - S. Thanigaivel; Saravanan Rajendran; Lalitha Gnanasekaran; Kit Wayne Chew; Dang Thuan Tran; Hoang-Dung Tran; Nguyen Khoi Nghia; Pau Loke Show (Environmental Chemistry Letters, 2023)

Current status and perspectives of algae-based bioplastics: A reviewed potential for sustainability - Wai Yan Cheah; Ah Choy Er; Kadaruddin Aiyub; Nazlina Haiza Mohd Yasin; Sue Lin Ngan; Kit Wayne Chew; Kuan Shiong Khoo; Tau Chuan Ling; Joon Ching Juan; Zengling Ma; Pau Loke Show (Algal Research, 2023)

Influence of Fe2O3 and bacterial biofilms on Cu(II) distribution in a simulated aqueous solution: A feasibility study to sediments in the Pearl River Estuary (PR China) - Tonni Agustiono Kurniawan; Waihung Lo; Mohd Hafiz Dzarfan Othman; Xue Liang; Hui Hwang Goh; Kit Wayne Chew (Journal of Environmental Management, 2023)

Smart systems in producing algae-based protein to improve functional food ingredients industries - Yi Ting Neo; Wen Yi Chia; Siew Shee Lim; Cheng Loong Ngan; Tonni Agustiono Kurniawan; Kit Wayne Chew (Food Research International, 2023)

From liquid waste to mineral fertilizer: Recovery, recycle and reuse of high-value macro-nutrients from landfill leachate to contribute to circular economy, food security, and carbon neutrality - Tonni Agustiono Kurniawan; Mohd Hafiz Dzarfan Othman; Xue Liang; Hui Hwang Goh; Kit Wayne Chew (Process Safety and Environmental Protection, 2023)

Artificial intelligence model for monitoring biomass growth in semi-batch Chlorella vulgaris cultivation - Angela Paul Peter; Kit Wayne Chew; Ashok Pandey; Sie Yon Lau; Saravanan Rajendran; Huong Yong Ting; Heli Siti Halimatul Munawaroh; Nguyen Van Phuong; Pau Loke Show (Fuel, 2023)

Application of regression and artificial neural network analysis of Red-Green-Blue image components in prediction of chlorophyll content in microalgae - Doris Ying Ying Tang; Kit Wayne Chew; Huong-Yong Ting; Yuk-Heng Sia; Francesco G. Gentili; Young-Kwon Park; Fawzi Banat; Alvin B. Culaba; Zengling Ma; Pau Loke Show (Bioresource Technology, 2023)

Microalgae identification: Future of image processing and digital algorithm - Jun Wei Roy Chong; Kuan Shiong Khoo; Kit Wayne Chew; Dai-Viet N. Vo; Deepanraj Balakrishnan; Fawzi Banat; Heli Siti Halimatul Munawaroh; Koji Iwamoto; Pau Loke Show (Bioresource Technology, 2023)

Strengthening waste recycling industry in Malang (Indonesia): Lessons from waste management in the era of Industry 4.0 - Tonni Agustiono Kurniawan; Christia Meidiana; Mohd Hafiz Dzarfan Othman; Hui Hwang Goh; Kit Wayne Chew (Journal of Cleaner Production, 2023)

Economic potential of bioremediation using immobilized microalgae-based microbial fuel cells - Jane-Yii Wu; Chyi-How Lay; Shir Reen Chia; Kit Wayne Chew; Pau Loke Show; Ping-Heng Hsieh; Chin-Chao Chen (Clean Technologies and Environmental Policy, 2021)

Microalgal-Bacterial Consortia as Future Prospect in Wastewater Bioremediation, Environmental Management and Bioenergy Production - Kuan Shiong Khoo; Wen Yi Chia; Kit Wayne Chew; Pau Loke Show (Indian Journal of Microbiology, 2021)

Microalgae for biofuels, wastewater treatment and environmental monitoring - Angela Paul Peter; Kuan Shiong Khoo; Kit Wayne Chew; Tau Chuan Ling; Shih-Hsin Ho; Jo-Shu Chang; Pau Loke Show (Environmental Chemistry Letters, 2021)

Optimization of production parameters of fish protein hydrolysate from Sarda Orientalis black muscle (by-product) using protease enzyme - Xuan Dong Bui; Cong Tuan Vo; Viet Cuong Bui; Thi My Pham; Thi Thu Hien Bui; Toan Nguyen-Sy; Thi Dong Phuong Nguyen; Kit Wayne Chew; M. D. Mukatova; Pau Loke Show (Clean Technologies and Environmental Policy, 2021)

Green technology for the industrial production of biofuels and bioproducts from microalgae: a review - Doris Ying Ying Tang; Guo Yong Yew; Apurav Krishna Koyande; Kit Wayne Chew; Dai-Viet N. Vo; Pau Loke Show (Environmental Chemistry Letters, 2020)

Improved physical properties and in vitro biocompatibility of chitosan composite scaffolds incorporated with a green filler on bone cells - Siew Shee Lim; Chye Jian Oon; Kit Wayne Chew; Jing Ying Yap; May Teng Lim; Derwin Su; Lai Yee Lee; Hwei-San Loh (Clean Technologies and Environmental Policy, 2020)

Isolation of protein from Chlorella sorokiniana CY1 using liquid biphasic flotation assisted with sonication through sugaring-out effect - Shir Reen Chia; Kit Wayne Chew; Pau Loke Show; Manickam Sivakumar; Tau Chuan Ling; Yang Tao (Journal of Oceanology and Limnology, 2019)

Extraction of agar from Eucheuma cottonii and Gelidium amansii seaweeds with sonication pretreatment using autoclaving method - Siti Sabariah Din; Kit Wayne Chew; Yu-Kaung Chang; Pau Loke Show; Siew Moi Phang; Joon Ching Juan (Journal of Oceanology and Limnology, 2019)